Revertant Mosaicism in Epidermolysis Bullosa - Cameron Meyer-Mueller; Mark J. Osborn; Jakub Tolar; Christina Boull; Christen L. Ebens (Biomedicines, 2022)
Epidermolysis bullosa (EB) is a group of genetic blistering diseases characterized by mechanically fragile skin and mucocutaneous involvement. Historically, disease management has focused on supportive care. The development of new genetic, cellular, and recombinant protein therapies has shown promise, and this review summarizes a unique gene and cell therapy phenomenon termed revertant mosaicism (RM). RM is the spontaneous correction of a disease-causing mutation. It has been reported in most EB subtypes, some with relatively high frequency, and has been observed in both keratinocytes and fibroblasts. RM manifests as identifiable patches of unaffected, blister-resistant skin and can occur through a variety of molecular mechanisms, including true back mutation, intragenic crossover, mitotic gene conversion, and second-site mutation. RM cells represent a powerful autologous platform for therapy, and leveraging RM cells as a therapeutic substrate may avoid the inherent mutational risks of gene therapy/editing. However, further examination of the genomic integrity and long-term functionality of RM-derived cells, as well in vivo testing of systemic therapies with RM cells, is required to realize the full therapeutic promise of naturally occurring RM in EB.